ASSISTÊNCIA PRÉ-CONCEPCIONAL E A PROMOÇÃO EM SAÚDE MATERNA NA ESTRATÉGIA DE SAÚDE DA FAMÍLIA - CELENE ARAUJO DA SILVA (2024)
A health promotion involves strategies relating to the formulation of public policies, the creation of favorable environments, strengthening community participation, fostering personal skills and reorienting health services. In this context, preconception care is one of the actions in promoting maternal health in the primary health care of the Unified Health System, which makes it possible to identify risk factors or diseases that could modify the usual course of a pregnancy, leading to negative outcomes for maternal and fetal health, as well as full exercise of human sexuality as a right. O objective of this study was to verify the knowledge of pregnant women and professionals working in the family health strategy unit on preconception care and its preconception care and its relevance to maternal health. A quantitative research was carried out by interviewing pregnant women over the age of over the age of eighteen linked to a family health strategy unit and a questionnaire was application of a questionnaire to health professionals from the health teams of the Strategy. Of the pregnant women interviewed (n=41), 61% said they were color and 51.2% had completed high school. More than half (63.4%) had not planned their pregnancy and the pre-conception tests were carried out mainly by those by those who had planned the pregnancy; 78.1% of the women 78.1% of the women did not know that the family health unit near their home offered preconception care to the population. Among the professionals interviewed (n=37), 83.2% reported not having received any training in the service on preconception care and 10.8% said they had already offered educational activities on the subject to the population or had followed some kind of protocol or flowchart in their care. It was observed that pregnant women and health professionals have a low level of knowledge about preconception care, a factor that needs to be changed to ensure that women and couples have more access to this women and couples have more access to this care and for there to be greater professionals who promote intersectoral actions aimed at improving maternal health, greater improving maternal health, a greater supply of pre-conception consultations in the Health Strategy and educational activities on this subject in health units and in the units, in the territory and areas covered by these units. Descriptors: preconception care; maternal health; family health strategy.